PENGARUH MODEL INKUIRI TERBIMBING MENGGUNAKAN LABORATORIUM VIRTUAL TERHADAP KETERAMPILAN ARGUMENTASI ILMIAH SISWA SMP - Tanti Lutfiatul Hidayah; Supeno Supeno; Ulin Nuha (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
Abstract: This study aims to determine the effect of applying a guided inquiry model using a virtual laboratory on the scientific argumentation skills of class IX students at SMP Negeri 11 Jember. This research is a type of quasi-experimental research with a quantitative approach. The population in this study were all class IX students of SMP Negeri 11 Jember, using 2 class samples, namely class IX F as the experimental class and IX E as the control class, with each class consisting of 32 students. The data collection technique used is test and non-test; the test consists of the posttest, and the non-test consists of observation, interviews, and documentation. The data analysis test used was the normality test and the independent sample t-test. The normality test results show that the data group was normally distributed. The independent sample t-test shows that the average scientific argumentation ability of the control class and the experimental class have significant differences.